Aplikasi E-Notetaking Berbasiskan Multimedia untuk Kegiatan Pencatatan - Yulianto, Budi; Pramita, Arizka; N., M. Fadly F.; N., Meidyta H. (Bina Nusantara University, 2011)
This article presents analysis and design of multimedia based e-notetaking application. The goals of the research are to optimize audio-visual usage in taking note, to organize notes to be tidied and categorized, and to make easy copying and sharing notes to other users. Output of the research is an e-notetaking application implemented on laptops. The designed e-notetaking application has features for users in taking notes by using notebook or netbook as easily as taking notes by using book.